2017
DOI: 10.1108/prt-01-2016-0016
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical performance and shape recovery behaviour of shape memory polymer nanocomposite incorporated with hexagonal boron nitride

Abstract: eprints@whiterose.ac.uk https://eprints.whiterose.ac.uk/ Reuse Unless indicated otherwise, fulltext items are protected by copyright with all rights reserved. The copyright exception in section 29 of the Copyright, Designs and Patents Act 1988 allows the making of a single copy solely for the purpose of non-commercial research or private study within the limits of fair dealing. The publisher or other rights-holder may allow further reproduction and re-use of this version -refer to the White Rose Research Onlin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The reduction of temperature leads to chain freezing and storage of entropic energy (Figure 13a4); however, with the increase of temperature as a result of heat or electrical current (Figure 13a5), the molecular chains are driven back to their lowest energy configuration (initial shape). Even though the literature on SMP/2D material nanocomposites is dominated by graphene-related materials, also MXenes could be in a similar manner for the creation of electrically and thermally conductive SMP composites, while boron nitride and its hybrids [225][226][227][228][229] could also offer an alternative. Overall, it can be concluded that the introduction of 2D fillers into shape memory epoxy resins at low filler contents can effectively lead to strong self-shaping structures and can avoid catastrophic failure.…”
Section: Shape Memory Propertiesmentioning
confidence: 99%
“…The reduction of temperature leads to chain freezing and storage of entropic energy (Figure 13a4); however, with the increase of temperature as a result of heat or electrical current (Figure 13a5), the molecular chains are driven back to their lowest energy configuration (initial shape). Even though the literature on SMP/2D material nanocomposites is dominated by graphene-related materials, also MXenes could be in a similar manner for the creation of electrically and thermally conductive SMP composites, while boron nitride and its hybrids [225][226][227][228][229] could also offer an alternative. Overall, it can be concluded that the introduction of 2D fillers into shape memory epoxy resins at low filler contents can effectively lead to strong self-shaping structures and can avoid catastrophic failure.…”
Section: Shape Memory Propertiesmentioning
confidence: 99%
“…SMPUs use their soft segments as transition segments for the shape-memory effect (SME). [25][26][27][28] However, although many researchers have tried to develop the fibers from pellets, unfortunately it is too difficult to create monofilaments due to the specific properties of PUs, such as mechanical strength, viscosity, flexibility and elasticity. 29,30 Narayana et al 31 synthesized a semicrystalline segmented PU in order to comprehend the fundamental aspects for precise optimization and control of memory stress in smart structures for applications such as compression stockings that require stimuli responsive force.…”
mentioning
confidence: 99%
“…Meanwhile, this acoustic metamaterials can be combined with intelligent materials to enhance their functionality. For example, it may be prepared from shape memory materials to have active deformation (Yao et al, 2018c;Lu et al, 2015), shape memory (Yao et al, 2018b) and controllable structure (Li et al, 2017;Yao et al, 2018a). Acoustic metamaterials ultimately achieve the adjustability of sound insulation frequency.…”
Section: Application Prospect Analysismentioning
confidence: 99%